Digital Leadership for the Chief Executive Officers (CEOs) of the Energy Industry in the Eastern Region - Yodmanee, Pekhanang (Arts of Management Journal, 2024)
This research aimed to study (1) the components of the digital leadership model among the CEOs of the energy industry in the Eastern Region. (2) To analyze the surveyed components of the digital leadership model among the CEOs of the energy industry in the Eastern region. The research is conducted using a mixed-methods approach. The sample consisted of 11 participants, including the CEOs of the energy industry and 400 employees within the Eastern Region’s energy industry. They were selected by employees working in industrial estates of approximately 40,000 people by the rules and a multistage random sampling. The instrument for collecting data was group interviews conducted with CEOs in the energy industry in the Eastern Region, with 11 participants selected through purposive sampling. Open-ended questions were employed to guide these interviews. The study collects a questionnaire survey with a reliability coefficient of 0.900. Analysis data from descriptive statistics include frequency analysis, percentage analysis, mean analysis, standard deviation analysis, exploratory factor analysis, and content analysis. The research results were found as follows: 1. The research findings on the digital leadership components of the energy industry in the Eastern Region derived from 11 CEOs of the energy industry in the Eastern Region by focus group, consisting of 7components: 1) digital vision; 2) digital knowledge and skills; 3) digital management; 4) digital culture; 5) digital collaboration network; 6) digital adaptation; and 7) digital strategy. 2. An exploratory factor analysis of the digital leadership components for CEOs was found to be suitable, encompassing digital vision, digital knowledge and skills, digital management, digital culture, digital collaboration network, digital adaptation, and digital strategy.